Dietary Phenolic Compounds: Their Health Benefits and Association with the Gut Microbiota - Yoko Matsumura; Masahiro Kitabatake; Shin-ichi Kayano; Toshihiro Ito (MDPI AG, 2023)
Oxidative stress causes various diseases, such as type II diabetes and dyslipidemia, while antioxidants in foods may prevent a number of diseases and delay aging by exerting their effects in vivo. Phenolic compounds are phytochemicals such as flavonoids which consist of flavonols, flavones, flavanonols, flavanones, anthocyanidins, isoflavones, lignans, stilbenoids, curcuminoids, phenolic acids, and tannins. They have phenolic hydroxyl groups in their molecular structures. These compounds are present in most plants, are abundant in nature, and contribute to the bitterness and color of various foods. Dietary phenolic compounds, such as quercetin in onions and sesamin in sesame, exhibit antioxidant activity and help prevent cell aging and diseases. In addition, other kinds of compounds, such as tannins, have larger molecular weights, and many unexplained aspects still exist. The antioxidant activities of phenolic compounds may be beneficial for human health. On the other hand, metabolism by intestinal bacteria changes the structures of these compounds with antioxidant properties, and the resulting metabolites exert their effects in vivo. In recent years, it has become possible to analyze the composition of the intestinal microbiota. The augmentation of the intestinal microbiota by the intake of phenolic compounds has been implicated in disease prevention and symptom recovery. Furthermore, the "brain-gut axis", which is a communication system between the gut microbiome and brain, is attracting increasing attention, and research has revealed that the gut microbiota and dietary phenolic compounds affect brain homeostasis. In this review, we discuss the usefulness of dietary phenolic compounds with antioxidant activities against some diseases, their biotransformation by the gut microbiota, the augmentation of the intestinal microflora, and their effects on the brain-gut axis.